Spatial distribution of the seismic hazard parameters in the seismogenic sources of Japan - TSAPANOS, T. M.; KORAVOS, G. CH.; PATSIA, C. I.; KOULARAS, D. TH. (Bulletin of the Geological Society of Greece, 2001)
The seismicity parameters in the seismogenic zones of Japan are estimated by the application of two different approaches. These are the maximum likelihood method as well as the Bayesian estimator is invoked in order to check the validity of the results. Both methods allow us to estimate the maximum regional (possible) earthquake M , the well known value β (b=ßloge) which is the slope of the magnitude-frequency relation and the mean activity rate /[ of the seismic events. The present study is focused in the first two parameters searching for any pattern on their geographical distribution through the sources of Japan. Two are the main assumptions adopted for both methods: 1) the seismic events are of Poissonian character and 2) the magnitude-frequency law is governed by Gutenberg-Richter type. The methods allow to account the influence of uncertainties of the earthquakes magnitude. Taking into account these properties we found that the values of M are different and bigger than the observed M^*x . The estimated b-values show very low values in the seismogenic sources 2 and 7. In comparison with other measurements from other authors these two sources suggested to be areas with very high probability for an large earthquake occurrence